Youth Categories and Drugs in Kosovo (2001-2014) - Sylejmani, Rrahman (European Journal of Multidisciplinary Studies, 2016)
The use of narcotic substances has become a phenomenon of great concern, not only in Kosovo but also in all other countries of the world. Although in Kosovo there are no accurate statistics on how many individuals are regular users of narcotic substances, it is calculated that there are approximately 20. 000 users. To add to this concerning issue, is the fact that the usage of narcotics in elementary and secondary school pupils and students. The objective of this paper is to offer a more realistic presentation of the cases of narcotic users from the new age groups. The goal is to identify the factors that influence the increase of this phenomenon, which is increasing specifically among the youth and is dangerous for public health and the public order and safety. The Kosovo Institutions have approved a National Strategy and action plan for Fighting the Use of Narcotic that is now being implemented. According to the Kosovo Police this strategy has had some positive results. Kosovo Police held more than 150 operations a year in all Kosovo, with a goal of issuing prosecutorial charges against suspected individuals that are active in different individual and group forms, regarding the cultivation and trafficking of drugs. According to the statistics from the Kosovo Police, during the 2012 there was a significant increase of confiscated narcotic substances in comparison with 2011, the percentage of the confiscation of Marihuana has increased around 400 percent. The use of narcotics among young people is considered as a growing phenomenon. I consider that this is primarily a result of the lack of awareness among the youth regarding the potential dangers for health and social aspects, and lack of specialized institutions for treatment and rehabilitation of the addicted individuals. Lack of appropriate institutional treatment of this phenomenon represents a danger not only for public health but for the safety and public order in general.